Questões sobre a morte e o morrer entre os egípcios e os hindus: conservação ou destruição do corpo? - Micsik, Beatriz Fonseca (2012)
This dissertation aims to analyze questions about the study of rites of passage, more specifically those that involve the Dying and Death in order to outline the importance of funerary rituals in the Hindu and Egyptian civilizations. Anchored in the structures of analysis about the death of literature from the areas of Anthropology, History and Egyptology norteio my reflections on the theories developed to understand the encounters with thinking about the myth of immortality, and the relations of related strains in obtaining direct of eternal life. With that as a starting point, develop questions about the different treatments of the bodies within the funerary rituals, especially rituals of mummification made in ancient Egypt, and the cremation used by Hindus to be able to outline the importance of relations between conservation and destruction of bodies. We understand that funeral rituals are part of the collective memory of civilizations, just as the archaeological remains are part of the documents-monuments preserved for the studies of history and archeology that form the reference, since they keep the traditions of old cultures. To illustrate this concept use me iconographic references to better illustrate the permanence of these cultures. The methodology used to analyze the organization initially predicted iconographic and pictorial description of the sets of books, and photographic collections specialist, found the Internet and photos taken by me to visit the British Museum in London and the Vatican in Italy